Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which expression is equivalent to [tex]\( (p - q)(x) \)[/tex], we need to start by computing [tex]\( p(x) \)[/tex] and [tex]\( q(x) \)[/tex]. Given:
[tex]\[ p(x) = x^2 - 1 \][/tex]
[tex]\[ q(x) = 5(x - 1) \][/tex]
Next, we calculate [tex]\( (p - q)(x) \)[/tex]:
[tex]\[ (p - q)(x) = p(x) - q(x) \][/tex]
Substituting the given expressions for [tex]\( p(x) \)[/tex] and [tex]\( q(x) \)[/tex]:
[tex]\[ (p - q)(x) = (x^2 - 1) - 5(x - 1) \][/tex]
Now, simplify the expression step-by-step:
1. Distribute the 5 in the term [tex]\( 5(x - 1) \)[/tex]:
[tex]\[ 5(x - 1) = 5x - 5 \][/tex]
2. Substitute this back into our main expression:
[tex]\[ (p - q)(x) = (x^2 - 1) - (5x - 5) \][/tex]
3. Simplify by distributing the negative sign through the second parenthesis:
[tex]\[ (p - q)(x) = x^2 - 1 - 5x + 5 \][/tex]
4. Combine like terms:
[tex]\[ (p - q)(x) = x^2 - 5x + 4 \][/tex]
Now, we need to match this simplified expression, [tex]\( x^2 - 5x + 4 \)[/tex], with one of the given choices.
Let's evaluate each given choice:
1. [tex]\( 5(x - 1) - x^2 - 1 \)[/tex]:
[tex]\[ 5(x - 1) - x^2 - 1 = 5x - 5 - x^2 - 1 = -x^2 + 5x - 6 \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
2. [tex]\( 5x - 1 - (x^2 - 1) \)[/tex]:
[tex]\[ 5x - 1 - (x^2 - 1) = 5x - 1 - x^2 + 1 = -x^2 + 5x \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
3. [tex]\( (x^2 - 1) - 5(x - 1) \)[/tex]:
[tex]\[ (x^2 - 1) - 5(x - 1) = (x^2 - 1) - 5x + 5 = x^2 - 5x + 4 \quad \text{(This matches our expression perfectly)} \][/tex]
4. [tex]\( (x^2 - 1) - 5x - 1 \)[/tex]:
[tex]\[ (x^2 - 1) - 5x - 1 = x^2 - 1 - 5x - 1 = x^2 - 5x - 2 \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
Thus, the correct expression equivalent to [tex]\( (p - q)(x) \)[/tex] is:
[tex]\[ \left(x^2-1\right)-5(x-1) \][/tex]
Therefore, the correct choice is:
[tex]\[ \boxed{\left(x^2-1\right)-5(x-1)} \][/tex]
[tex]\[ p(x) = x^2 - 1 \][/tex]
[tex]\[ q(x) = 5(x - 1) \][/tex]
Next, we calculate [tex]\( (p - q)(x) \)[/tex]:
[tex]\[ (p - q)(x) = p(x) - q(x) \][/tex]
Substituting the given expressions for [tex]\( p(x) \)[/tex] and [tex]\( q(x) \)[/tex]:
[tex]\[ (p - q)(x) = (x^2 - 1) - 5(x - 1) \][/tex]
Now, simplify the expression step-by-step:
1. Distribute the 5 in the term [tex]\( 5(x - 1) \)[/tex]:
[tex]\[ 5(x - 1) = 5x - 5 \][/tex]
2. Substitute this back into our main expression:
[tex]\[ (p - q)(x) = (x^2 - 1) - (5x - 5) \][/tex]
3. Simplify by distributing the negative sign through the second parenthesis:
[tex]\[ (p - q)(x) = x^2 - 1 - 5x + 5 \][/tex]
4. Combine like terms:
[tex]\[ (p - q)(x) = x^2 - 5x + 4 \][/tex]
Now, we need to match this simplified expression, [tex]\( x^2 - 5x + 4 \)[/tex], with one of the given choices.
Let's evaluate each given choice:
1. [tex]\( 5(x - 1) - x^2 - 1 \)[/tex]:
[tex]\[ 5(x - 1) - x^2 - 1 = 5x - 5 - x^2 - 1 = -x^2 + 5x - 6 \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
2. [tex]\( 5x - 1 - (x^2 - 1) \)[/tex]:
[tex]\[ 5x - 1 - (x^2 - 1) = 5x - 1 - x^2 + 1 = -x^2 + 5x \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
3. [tex]\( (x^2 - 1) - 5(x - 1) \)[/tex]:
[tex]\[ (x^2 - 1) - 5(x - 1) = (x^2 - 1) - 5x + 5 = x^2 - 5x + 4 \quad \text{(This matches our expression perfectly)} \][/tex]
4. [tex]\( (x^2 - 1) - 5x - 1 \)[/tex]:
[tex]\[ (x^2 - 1) - 5x - 1 = x^2 - 1 - 5x - 1 = x^2 - 5x - 2 \quad \text{(This is not equivalent to } x^2 - 5x + 4) \][/tex]
Thus, the correct expression equivalent to [tex]\( (p - q)(x) \)[/tex] is:
[tex]\[ \left(x^2-1\right)-5(x-1) \][/tex]
Therefore, the correct choice is:
[tex]\[ \boxed{\left(x^2-1\right)-5(x-1)} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.